Tai Chi Combined With Resistance Training for Adults Aged 50 Years and Older: A Systematic Review. Issue 1 (January 2020) - Qi, Meiling; Moyle, Wendy; Jones, Cindy; Weeks, Benjamin
Abstract : Background and Purpose: Despite Tai Chi and resistance training being recommended as suitable exercise for older adults, there are no systematic reviews synthesizing the effectiveness of a combination of Tai Chi and resistance training on health promotion of older adults. This study aimed to review the existing literature regarding the effect of Tai Chi and resistance training on physical health, mental health, pain, health-related quality of life, and age-related impairment in adults aged 50 years and older. Methods: A systematic review was conducted to report the health outcomes of Tai Chi combined with resistance training research in adults aged 50 years and older. Articles were identified by searching PubMed, Scopus, Web of Science, CINAHL, MEDLINE, Physiotherapy Evidence Database (PEDro), and the Cochrane library using search terms representing "Tai Chi" and "resistance" and "older adults." Quantitative experimental studies with participants aged 50 years and older, where one of the interventions was Tai Chi and resistance training, were included. Results and Discussion: The literature search yielded 648 articles from which 7 met the inclusion criteria. Collectively, the studies involved 703 participants aged 50 years and older, including healthy older adults, older adults with history of falls, postmenopausal women, and people diagnosed with end-stage hip osteoarthritis. Studies included different Tai Chi forms in combination with various types of resistance training. Training sessions were 2 to 7.5 h/wk and lasted between 12 weeks and 12 months. After long-term Tai Chi and resistance training, the participants showed significant improvement in upper and lower extremity muscle strength, aerobic endurance, balance, and mobility. However, 1 study failed to show improvement in Functional Movement Screening compared with traditional Tai Chi and nonexercise groups. No study examined the effects of Tai Chi and resistance training on health-related quality of life, fear of falling, or mental health in adults aged 50 years and older. Conclusions: The review supports that Tai Chi in combination with resistance training improves physical function and muscle strength in adults aged 50 years and older.